The Factors Influencing the Sense of Home in Nursing Homes: A Systematic Review from the Perspective of Residents. (23rd May 2016) - Rijnaard, M. D.; van Hoof, J.; Janssen, B. M.; Verbeek, H.; Pocornie, W.; Eijkelenboom, A.; Beerens, H. C.; Molony, S. L.; Wouters, E. J. M.
Abstract : Purpose . To provide an overview of factors influencing the sense of home of older adults residing in the nursing home. Methods . A systematic review was conducted. Inclusion criteria were (1) original and peer-reviewed research, (2) qualitative, quantitative, or mixed methods research, (3) research about nursing home residents (or similar type of housing), and (4) research on the sense of home, meaning of home, at-homeness, or homelikeness. Results . Seventeen mainly qualitative articles were included. The sense of home of nursing home residents is influenced by 15 factors, divided into three themes: (1) psychological factors (sense of acknowledgement, preservation of one's habits and values, autonomy and control, and coping); (2) social factors (interaction and relationship with staff, residents, family and friends, and pets) and activities; and (3) the built environment (private space and (quasi-)public space, personal belongings, technology, look and feel, and the outdoors and location). Conclusions . The sense of home is influenced by numerous factors related to the psychology of the residents and the social and built environmental contexts. Further research is needed to determine if and how the identified factors are interrelated, if perspectives of various stakeholders involved differ, and how the factors can be improved in practice.